Sporadic Dips from Extended Debris Transiting the Metal-rich White Dwarf SBSS 1232+563 - J. J. Hermes; Joseph A. Guidry; Zachary P. Vanderbosch; Mariona Badenas-Agusti; Siyi Xu; Malia L. Kao; Antonio C. Rodriguez; Keith Hawkins (The Astrophysical Journal)
We present the discovery of deep but sporadic transits in the flux of SBSS 1232+563, a metal-rich white dwarf polluted by disrupted exoplanetary debris. Nearly 25 yr of photometry from multiple sky surveys reveal evidence of occasional dimming of the white dwarf, most notably evident in an 8 month long event in 2023 that caused a >40% drop in flux from the star. In-transit follow-up shows additional short-timescale (minutes- to hours-long) dimming events. Transiting Exoplanet Survey Satellite photometry suggests a coherent 14.842 hr signal that could represent the dominant orbital period of debris. Six low-resolution spectra collected at various transit depths over two decades show no evidence of significant changes in the observed elemental abundances. SBSS 1232+563 demonstrates that debris transits around white dwarfs can be sporadic, with many years of inactivity before large-amplitude dimming events.